Nanographenes and Graphene Nanoribbons with Zigzag-Edged Structures - Liu, Junzhi; Berger, Reinhard; Muellen, Klaus; Feng, Xinliang (Springer New York LLC, 2017)
Compared with armchair-edged nanographenes (NGs) and graphene nanoribbons (GNRs), graphene nanostructures with zigzag edge peripheries display unique electronic, magnetic, and photophysical properties resulting from the spin-polarized state at the zigzag edges. More interestingly, some possess prominent biradical/polyradical character in the ground state. Thanks to the development of chemistry in recent decades, such NGs and GNRs with unique zigzag peripheries are now synthetically accessible. This chapter discusses several strategies for the synthesis of zigzag-edged NGs and GNRs, their structural characterization, physical properties, and potential applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Graphene nanoribbons; Hetroartoms; Nanographenes; Radicals; Zigzag-Edge